Improving Hydrogen Release From Oxygen-Functionalized LOHC Molecules by Ru Addition to Pt/C Catalysts - Maurer, Lukas; Pham, Chuyen v.; Fritsch, Birk; Jeppesen, Henrik S.; Etter, Martin; Hutzler, Andreas; Neder, Reinhard; Wolf, Moritz; Auer, Franziska; Thiele, Simon; Wasserscheid, Peter (ChemCatChem, 2024)
Bimetallic PtRu/C catalysts have been prepared by depositing Ru onto a commercial Pt/C catalyst and subsequent thermal annealing. Different Pt : Ru ratios of 1 : 1, 2 : 1, 4 : 1, 8 : 1, and 16 : 1 have been investigated with annealing temperatures of 350 and 500 °C. Using X-ray diffraction (XRD), synchrotron powder X-ray diffraction (SPXRD) combined with pair distribution function (PDF) analysis and scanning transmission electron microscopy with energy dispersive X-ray spectrum imaging (STEM-EDXS), we show that diffusion of Ru into the fcc crystal structure of the Pt nanoparticles takes place during thermal annealing. Partial segregation and the formation of Pt nanoclusters on the bimetallic surface was observed depending on the Pt : Ru ratio. The annealing process does not only cause a high Pt dispersion but also affects the electronic structure of the Pt surface by broadening the d-band thus facilitating the product's desorption from the surface of the bimetallic particle. These beneficial effects have been exemplified for the catalytic dehydrogenation of dicyclohexylmethanol, a promising hydrogen carrier compound with 7.2 wt% hydrogen capacity. The most active catalyst material among the tested supported alloys and monometallic reference materials was Pt4Ru1/C after annealing at 500 °C, which increased the hydrogen release productivity by 65 % compared to the unmodified Pt/C catalyst.
CRIS-Team Scopus Importer:2024-07-19
Keywords: Alloys; Chemical hydrogen storage; Dehydrogenation; Heterogeneous catalysis; LOHC; Platinum; Ruthenium